Poverty in a rich society : the case of Hong Kong - Lau, Maggie K. W.; Gordon, David, 1959- (The Chinese University Press, 2017)
Hong Kong has remained a wealthy financial hub but its income inequality is greater than that in any developed economy. The growing unequal income distribution and poverty in Hong Kong have aroused public concern. This book brings together some of Hong Kong's and the U.K.'s leading experts to examine poverty in Hong Kong from three perspectives: (1) public understanding of poverty, and the extent of poverty and social exclusion in Hong Kong society, (2) poverty and health as well as child poverty and educational opportunities in Hong Kong, and (3) effectiveness of poverty alleviation measures in Hong Kong. On this basis, this book advances the theory and practice of poverty and social exclusion measurement, and will inspire comparative research and policy analyses for better policy initiatives.